Plankton Multiproxy Analyses in the Northern Patagonian Shelf, Argentina: Community Structure, Phycotoxins, and Characterization of Toxic Alexandrium Strains - Guinder, Valeria A.; Tillmann, Urban; Krock, Bernd; Delgado, Ana L.; Krohn, Torben; Garzón Cardona, John E.; Metfies, Katja; López Abbate, Celeste; Silva, Ricardo; Lara, Rubén (Frontiers in Marine Science, 2018)
The extensive Argentine continental shelf supports high plankton productivity and fish catches. In particular, El Rincón coastal area and the adjacent shelf fronts (38.5–42º S, 58.5–62º W) comprise diverse habitats and hold species of economic and ecological value. So far, studies of the microbial community at the base of the food web remain scarce. Here we describe the early spring plankton (>5-200 µm) structure in terms of abundance, biomass, species composition, functional groups and phycotoxin profiles in surface waters of El Rincón in September 2015. Diatoms were the most abundant and the largest contributors to carbon biomass at most stations. They dominated in coastal and inner-shelf (depths <50 m) while dinoflagellates and small flagellates (<15 µm) dominated offshore at middle-shelf waters (depth 100 m). Likewise, large (>20 µm) heterotrophic protists, e.g. various ciliates and dinoflagellates species were more abundant offshore. Scanning of phycotoxins in the field disclosed that paralytic shellfish poisoning (PSP) toxins were dominated by gonyautoxins-1/4 (GTX1/4). Lipophilic toxins were detected in low abundance, e.g. domoic acid (DA), although a bloom of Pseudo-nitzschia spp. (up to 3.6 x 105 cells L-1) was detected at inner-shelf stations. Pectenotoxin-2 (PTX-2) and 13-desmethyl spirolide C (SPX-1) were the most abundant in the field. PTX-2 co-occurred with Dinophysis spp., mainly D. tripos, while SPX-1 dominated at middle-shelf stations, where cells of Alexandrium catenella (1 strain) and A. ostenfeldii (3 strains) were isolated. The quantitative PSP profiles of the Alexandrium strains differed significantly from the field profiles. Moreover, the three A. ostenfeldii strains proved to be PSP producers and additionally produced 5 novel spirolides. Phylogenetic analyses of these first strains from the South Atlantic disclosed a new ribotype group suggesting a biogeographical distinction of the population. The plankton survey presented here contributes with baseline knowledge to evaluate potential ecosystem changes and to track the global distribution of toxigenic species.